2019
DOI: 10.1137/19m1246274
|View full text |Cite
|
Sign up to set email alerts
|

Large-Scale Bayesian Spatial-Temporal Regression with Application to Cardiac MR-Perfusion Imaging

Abstract: We develop a hierarchical Bayesian approach for the inference of large-scale spatial-temporal regression as often encountered in the analysis of imaging data. For each spatial location a linear temporal Gaussian regression model is considered. Large-scale refers to the large number of spatially distributed regression parameters to be inferred. The spatial distribution of the sought regression parameters, which typically represent physical quantities, is assumed to be smooth and bounded from below. Truncated, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Inverse problems are frequently encountered in metrology. Examples include applications such as scatterometry [1], magnetic resonance imaging (MRI) [2], magnetic resonance fingerprinting [3,4], cardiac perfusion [5], computed tomography [6], and spectroscopy [7], to mention just a few. Statistical modeling is an appropriate tool to tackle inverse problems and provides the basis for established procedures such as maximum likelihood estimation from classical statistics [8] or the application of Bayesian inference [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inverse problems are frequently encountered in metrology. Examples include applications such as scatterometry [1], magnetic resonance imaging (MRI) [2], magnetic resonance fingerprinting [3,4], cardiac perfusion [5], computed tomography [6], and spectroscopy [7], to mention just a few. Statistical modeling is an appropriate tool to tackle inverse problems and provides the basis for established procedures such as maximum likelihood estimation from classical statistics [8] or the application of Bayesian inference [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is also common to include expected properties of the solution. For example, spatial smoothness can be expressed by a Gaussian Markov random field (GMRF) [18] taken as a prior distribution (see applications such as cardiac perfusion [5], nano-spectroscopy [19] and magnetic resonance fingerprinting [11]). Another thriving field of research deals with the determination of prior knowledge from data.…”
Section: Introductionmentioning
confidence: 99%
“…Bayesian approaches to spatial-temporal modeling have shown to be a versatile tool to capture complex phenomena and handle imbalanced or missing observations [1,2]. Among their wide range of applications are climate and weather modeling [3], disease mapping [4,5], medical image analysis [6,7], traffic management [8,9], environmental changes [10,11,12] and health economic evaluations [13]. We see growing amounts of data available to describe these phenomena and increasingly sophisticated models to characterize them [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…We note that the application of HBMs to myocardial perfusion modelling has been proposed in four previous publications: Schmid et al (2007), Schmid (2011), Lehnert et al (2019) and Scannell et al (2020). Here, the emphasis has been on the estimation of the MBF per se, and the authors have demonstrated that the MBF parameters can be more accurately estimated than with traditional methods, such as non-hierarchical non-linear regression, particularly in regimes where the signal-to-noise ratio (SNR) is low (see Scannell et al, 2020 for details).…”
mentioning
confidence: 99%
“…Schmid (2011) extended the modelling in Schmid et al (2007) by importing spatio-temporal constrains to the B-spline model using Gaussian MRF. Lehnert et al (2019) illustrated an HBM method to analyse the myocardial perfusion DCE-MRI. In this method, a large-scale Bayesian spatio-temporal regression method was applied to model the data.…”
mentioning
confidence: 99%